2004
DOI: 10.1007/s11745-004-1274-7
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age and birth weight in relation to n−3 fatty acids among inuit (Canada)

Abstract: Seafood consumption during pregnancy carries both benefits (high n-3 FA intake) and risks (exposure to environmental contaminants) for the developing fetus. We determined the impacts of marine n-3 FA and environmental contaminants on gestational age (GA) of Nunavik women and the anthropometric characteristics of their newborns. FA and contaminant (polychlorinated biphenyls and mercury) concentrations were measured in cord plasma of Nunavik newborns (n = 454) and compared with those of a group of newborns (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 89 publications
(99 reference statements)
0
51
3
Order By: Relevance
“…Data points for the lowest quintile of mercury exposure in the upper quartile of seafood intake (n 10) and for highest quintile of mercury exposure in the lowest quartile of seafood intake (n 39) are not shown due to low statistical power Our findings of estimated levels of dietary Hg exposure are in agreement with what was found in a study of Swedish women of childbearing age, as well as similar to dietary exposure levels reported worldwide in women of childbearing age (44,45) . Studies of maternal Hg exposure and infant birth weight have until recently not reported significant associations (25,46,47) . Although studies have found associations between exposure to other environmental contaminants accumulating in fish and seafood and fetal growth (48,49) , it is only recently that reports of a direct adverse association to low-level Hg exposure have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Data points for the lowest quintile of mercury exposure in the upper quartile of seafood intake (n 10) and for highest quintile of mercury exposure in the lowest quartile of seafood intake (n 39) are not shown due to low statistical power Our findings of estimated levels of dietary Hg exposure are in agreement with what was found in a study of Swedish women of childbearing age, as well as similar to dietary exposure levels reported worldwide in women of childbearing age (44,45) . Studies of maternal Hg exposure and infant birth weight have until recently not reported significant associations (25,46,47) . Although studies have found associations between exposure to other environmental contaminants accumulating in fish and seafood and fetal growth (48,49) , it is only recently that reports of a direct adverse association to low-level Hg exposure have been published.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reasons why the maximum cord-blood T-Hg level was about 70 times higher than the minimum level are that daily fi sh intake and the kinds of fi sh consumed differed markedly among study populations and that the method and quality control of mercury analyses differed among these laboratories. For instance, since arctic or subarctic inhabitants used to eat seal or whale (Dennis and Fehr 1975;Bjerregaard and Hansen 2000;Lucas et al 2004;Grandjean et al 2005), the cord-blood T-Hg concentrations in these areas seemed to be high. Also, Dallaire et al (2003) analyzed 248 cordblood samples of Inuit infants born in Nunavik (Québec, Canada), which were collected from 1994 to 2001, and observed a signifi cant reduction of T-Hg concentrations in cord blood (8.3% per year), as well as polychlorinated biphenyls (PCBs) and lead, whereas the average mercury concentrations in Faroese pregnant women decreased because of a dietary advisory issued by the health authorities in 1998 .…”
Section: Analytical Methods Of Mercury In Cord Blood and Tissuementioning
confidence: 99%
“…Cord blood: Lead Buchet et al 1978;Lauwerys et al 1978;Tsuchiya et al 1984;Truska et al 1989;Soong et al 1991;Grandjean et al 1992;Ong et al 1993;Klopov 1998;Rhainds et al 1999;Dallaire et al 2003;Lucas et al 2004;Vigeh et al 2006;Walker et al 2006Cadmium Buchet et al 1978Lauwerys et al 1978;Tsuchiya et al 1984;Truska et al 1989;Soong et al 1991;Ong et al 1993;Klopov 1998;Vigeh et al 2006;Walker et al 2006Manganese Tsuchiya et al 1984Vigeh et al 2006Arsenic Soong et al 1991 Antimony and cobalt Vigeh et al 2006 Polychlorinated biphenyls (PCBs) Rhainds et al 1999;Grandjean et al 2001;Dallaire et al 2003;Lucas et al 2004 Pesticides Rhainds et al 1999 Cord tissue: Lead Noda et al 1983;Tsuchiya et al 1984;Sugiyama et al 1996;Shaheen et al 2004Cadmium Noda et al 1983Tsuchiya et al 1984;Sugiyama et al 1996Manganese Noda et al 1983Tsuchiya et al 1984;Shaheen et al 2004…”
Section: Toxicants Authorsmentioning
confidence: 99%
“…In a Canadian study, the associations between n-3 LCPUFA and environmental contaminants (such as mercury, lead and PCBs) and gestational age and birth weight were investigated (Lucas et al, 2004). n-3 LCPUFA and contaminant concentrations were measured in cord plasma in a seafood eating population (Nunavik, n = 454) and in a comparison group from southern Québec (n = 29).…”
Section: Developmental Toxicity Other Than Neurotoxicity and Immunotomentioning
confidence: 99%